Glue and brushing method thereof

By applying a glue containing specific components on the front of the back contact solar cell to form a protective film, the problem of easy scratches in the battery cell is solved, and the conversion efficiency of the battery cell and the power generation of the system are significantly improved.

CN119410277APending Publication Date: 2025-02-11JINKO SOLAR CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411586653.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

Back contact solar cells are susceptible to external forces such as mechanical friction and collision during manufacturing, transportation and installation, resulting in scratches on the surface of the battery cell and reducing conversion efficiency and system power generation.

Method used

A glue including a matrix resin, functional monomer, active diluent, photoinitiator and other additives is provided, and is applied on the front of the back contact battery by a printing device or a spraying device to form a protective film to resist external force.

Benefits of technology

The glue has excellent adhesion and wear resistance, significantly reduces the scratch rate of the battery cell, maintains high conversion efficiency, and has a better appearance effect than the epoxy system glue.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410277A_ABST
    Figure CN119410277A_ABST
Patent Text Reader

Abstract

The invention provides glue and a brushing method thereof. The glue comprises matrix resin, a functional monomer, a reactive diluent, a photoinitiator and other auxiliaries. In the glue, the mass fraction of the matrix resin is 20%-35%, the mass fraction of the functional monomer is 5%-10%, the mass fraction of the reactive diluent is 40%-55%, the mass fraction of the photoinitiator is 2%-6%, the matrix resin comprises methyl methacrylate, styrene and hydroxyethyl methylacrylate, and the functional monomer comprises methyl methacrylate, styrene and hydroxyethyl methylacrylate. The functional monomer is dimethylaminoethyl methacrylate. The invention further provides a brushing method of the glue, the glue is brushed on the front surface of the back contact battery by using a printing device or a spraying device to form a protective film, and the problem that the conversion efficiency of a battery piece is reduced due to the fact that the front surface of the back contact battery is easily scratched is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of photovoltaic technology, and in particular to a glue and a coating method thereof. Background Art

[0002] As an important product type in the photovoltaic field, back-contact solar cells have attracted widespread attention for their high efficiency, high reliability and good stability. However, during the manufacturing, transportation and installation of back-contact solar cells, scratches are easily generated on the surface of the cells due to various external forces, such as mechanical friction and collision. These scratches not only affect the appearance of the cells, but more importantly, they will reduce the conversion efficiency of the cells and reduce the power generation of the photovoltaic system, thus affecting the economic benefits of the entire system.

[0003] At present, although there are some measures for protecting the surface of battery cells on the market, such as film pasting, spraying protective layer, etc., these methods have certain limitations in practical applications. For example, although the film pasting method can effectively protect the surface of battery cells, it increases the production cost, and the film may fall off and bubble during the use of the battery cells, affecting the long-term stability of the battery cells; and the traditional spraying protective layer may lead to poor protection due to improper material selection or poor painting process, and even affect the photoelectric performance of the battery cells. Although some glues have been developed to prevent battery cells from being scratched, these glues often have problems such as high viscosity, slow curing speed, and easy cracking after curing, which cannot meet the high requirements of back-contact solar cells for protective layers.

[0004] In order to solve the problem that the front side of the back contact battery is easily scratched, resulting in reduced conversion efficiency of the battery cell, the present application provides a glue and a method for applying the glue. Summary of the invention

[0005] In order to solve the problem that the front of the back contact battery is easily scratched, resulting in a decrease in the conversion efficiency of the battery cell, the present application provides a glue and a method for applying it. The glue includes a base resin, a functional monomer, a reactive diluent, a photoinitiator and other additives. In the glue, the mass fraction of the base resin is 20% to 35%, the mass fraction of the functional monomer is 5% to 10%, the mass fraction of the reactive diluent is 40% to 55%, and the mass fraction of the photoinitiator is 2% to 6%. The base resin includes methyl methacrylate, styrene and hydroxyethyl methacrylate, and the functional monomer is dimethylaminoethyl methacrylate.

[0006] The glue provided in this application has excellent adhesion and wear resistance, can form a protective film on the surface of the battery, effectively resist external forces such as mechanical friction and collision, and significantly reduce the scratch rate of the battery cell. It solves the problem that the front of the back-contact battery is easily scratched, resulting in reduced conversion efficiency of the battery cell. At the same time, no glue spots can be observed on the appearance of the components prepared with the acrylic system UV-curing glue, which has a better appearance effect than the epoxy system glue.

[0007] Optionally, in the glue, the mass fraction of methyl methacrylate is 10% to 15%, the mass fraction of styrene is 5% to 10%, and the mass fraction of hydroxyethyl methacrylate is 5% to 10%.

[0008] Optionally, the reactive diluent includes dipentaerythritol hexaacrylate and β-carboxyethyl acrylate, and in the glue, the mass fraction of the dipentaerythritol hexaacrylate is 15% to 20%, and the mass fraction of the β-carboxyethyl acrylate is 25% to 35%.

[0009] Optionally, the photoinitiator includes 2,4,6-trimethylbenzoyl-diphenylphosphine oxide and methyl benzoylformate.

[0010] Optionally, in the glue, the mass fraction of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide is 1% to 2%, and the mass fraction of methyl benzoylformate is 1% to 4%.

[0011] The present application also provides a coating method for coating the glue described in any one of the above items, specifically comprising: applying a coating device to the front side of a back contact battery to obtain a scratch-resistant battery.

[0012] Optionally, the anti-scratch battery coating area accounts for 2.5% to 3.8% of the front area of ​​the back contact battery.

[0013] Optionally, the method is a single-time coating, and the anti-scratch battery surface glue has a thickness of 13 μm to 18 μm after curing.

[0014] Optionally, the anti-scratch battery coating area accounts for 2.8% of the front area of ​​the back contact battery, and the thickness of the anti-scratch battery surface glue after curing is 15 μm.

[0015] Optionally, the coating device is a printing device or a spraying device, the spraying device includes a glue spray nozzle and a glue container, the glue spray nozzle is connected to the glue container, the glue spray nozzle is connected to a UV lamp, an insulation device is arranged in the glue container, and the temperature in the glue container is 80°C to 90°C.

[0016] The present application provides a glue and a method for applying the glue. The glue includes a base resin, a functional monomer, a reactive diluent, a photoinitiator and other additives. In the glue, the mass fraction of the base resin is 20% to 35%, the mass fraction of the functional monomer is 5% to 10%, the mass fraction of the reactive diluent is 40% to 55%, and the mass fraction of the photoinitiator is 2 to 6%. The base resin includes methyl methacrylate, styrene and hydroxyethyl methacrylate, and the functional monomer is dimethylaminoethyl methacrylate. The present application also provides a method for applying the above-mentioned glue, wherein the glue is applied to the front of the back contact battery using a printing device or a spraying device to form a protective film, thereby solving the problem that the front of the back contact battery is easily scratched, resulting in a decrease in the conversion efficiency of the battery cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the technical solution of the present application, the drawings required for use in the embodiments are briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without any creative work.

[0018] Figure 1 Schematic diagram of the appearance of the component prepared with epoxy system glue;

[0019] Figure 2 A schematic diagram of the appearance of a component prepared with the acrylic system glue provided in this application;

[0020] Figure 3 Schematic diagram of the printing screen provided for this application;

[0021] Figure 4 A schematic diagram of a glue coating pattern for the coating method provided in this application. DETAILED DESCRIPTION

[0022] The following embodiments are described in detail, and examples thereof are shown in the accompanying drawings. When the following description refers to the drawings, unless otherwise indicated, the same numbers in different drawings represent the same or similar elements. The implementations described in the following embodiments do not represent all implementations consistent with the present application. They are only examples of systems and methods consistent with some aspects of the present application as detailed in the claims.

[0023] In order to solve the problem that the front of the back contact battery is easily scratched, resulting in a decrease in the conversion efficiency of the battery cell, the present application provides a glue and a method for applying it. The glue includes a base resin, a functional monomer, a reactive diluent, a photoinitiator and other additives. In the glue, the mass fraction of the base resin is 20% to 35%, the mass fraction of the functional monomer is 5% to 10%, the mass fraction of the reactive diluent is 40% to 55%, and the mass fraction of the photoinitiator is 2% to 6%. The base resin includes methyl methacrylate, styrene and hydroxyethyl methacrylate, and the functional monomer is dimethylaminoethyl methacrylate.

[0024] The glue provided in this application has excellent adhesion and wear resistance, and can form a protective film on the battery surface, effectively resisting external forces such as mechanical friction and collision, and significantly reducing the scratch rate of the battery cell. This solves the problem that the front of the back-contact battery is easily scratched, resulting in reduced conversion efficiency of the battery cell.

[0025] As needed, other additives include appropriate amounts of leveling agents (such as BYK-300, BYK-348, etc.) and defoamers (such as TEGOFoamex 810, 825, etc.) to improve the leveling of the glue and eliminate bubbles.

[0026] like Figure 1 The figure shows the appearance of the components prepared with epoxy system glue. Figure 2 The schematic diagram of the appearance of the component prepared with the acrylic system glue provided in this application clearly shows that no glue spots can be observed on the appearance of the component prepared with the acrylic system UV-curing glue, which has a better appearance effect than the epoxy system glue.

[0027] In some embodiments, in the glue, the mass fraction of methyl methacrylate is 10% to 15%, the mass fraction of styrene is 5% to 10%, and the mass fraction of hydroxyethyl methacrylate is 5% to 10%.

[0028] For example, in the glue, the mass fraction of methyl methacrylate is 11%, 12%, 13% or 14%, the mass fraction of styrene is 6%, 7%, 8% or 9%, and the mass fraction of hydroxyethyl methacrylate is 6%, 7%, 8% or 9%.

[0029] In some embodiments, the reactive diluent includes dipentaerythritol hexaacrylate and β-carboxyethyl acrylate. In the glue, the mass fraction of the dipentaerythritol hexaacrylate is 15% to 20%, and the mass fraction of the β-carboxyethyl acrylate is 25% to 35%.

[0030] For example, in the glue, the mass fraction of dipentaerythritol hexaacrylate is 16%, 17%, 18%, 19% or 20%, and the mass fraction of β-carboxyethyl acrylate is 26%, 28%, 30%, 32% or 34%.

[0031] In some embodiments, the photoinitiator includes 2,4,6-trimethylbenzoyl-diphenylphosphine oxide and methyl benzoylformate.

[0032] In some embodiments, in the glue, the mass fraction of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide is 1% to 2%, and the mass fraction of methyl benzoylformate is 1% to 4%.

[0033] For example, the mass fraction of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide in the glue is 1.2%, 1.5%, 1.6%, 1.8% or 1.9%, and the mass fraction of methyl benzoylformate is 1.5%, 2%, 2.7%, 3% or 3.6%. The glue provided in the embodiment of the present application can be used to brush the front of the back contact battery. The glue brushed on the front of the back contact battery forms a protective film after curing. The protective film can effectively reduce the scratch rate of the battery cell, and the setting of the protective film has little effect on light loss, so that the back contact battery still has a high conversion efficiency.

[0034] The present application also provides a coating method for coating the glue described in any one of the above items, specifically comprising: applying a coating device to the front side of a back contact battery to obtain a scratch-resistant battery.

[0035] In some embodiments, the anti-scratch battery coating area accounts for 2.5% to 3.8% of the front area of ​​the back contact battery. Figure 4 As shown, some glue painting patterns of this application when painting the front of the battery. When the pattern accounts for 2.80% of the area, under the premise of good protection effect (no scratches), the battery efficiency loss △Eta <0.05.

[0036] For example, the anti-scratch battery coating area accounts for 2.6%, 2.8%, 3%, 3.2%, 3.4% or 3.6% of the area of ​​the front side of the back contact battery.

[0037] The glue solidifies to form a protective film, and the protective film can be composed of multiple discrete patterns, that is, glue is applied to different areas of the front side.

[0038] In some embodiments, the method is a single brushing, and the anti-scratch battery surface glue has a thickness of 13 μm to 18 μm after curing. It is understood that the glue forms a protective film after curing, that is, the thickness of the protective film is 13 μm to 18 μm.

[0039] Within this thickness range, it can ensure that the protective film formed by the curing of the glue has sufficient protection for the back-contact battery, and can minimize the light loss problem caused by the protective film, ensuring that the back-contact battery has a high conversion efficiency.

[0040] For example, the anti-scratch battery surface glue has a thickness of 13.5 μm, 14 μm, 15 μm, 16 μm or 17 μm after curing.

[0041] In some more specific examples, the anti-scratch battery surface glue may have a thickness of 14 μm to 16 μm after curing.

[0042] In some embodiments, the anti-scratch battery coating area accounts for 2.8% of the front area of ​​the back contact battery, and the thickness of the anti-scratch battery surface glue after curing is 15 μm.

[0043] In some embodiments, the coating device is a printing device or a spraying device, and the printing device includes a printing screen.

[0044] In some embodiments, the printing screen is used to print glue on the above-mentioned battery sheet, and the glue pattern printed by the printing screen is as follows: Figure 3 shown.

[0045] In some embodiments, the printing screen is Figure 4 As shown, the mesh holes of the printing screen correspond one-to-one with the preset glue points, which can reduce the possibility of glue misalignment when covering the grid lines, thereby improving the accuracy of the printing process, which is beneficial to improving the production yield of the battery cell, so that the battery cell has good working performance after assembly.

[0046] In some embodiments, the spraying device includes a control module and a glue spraying module, the glue spraying module includes a glue spraying nozzle and a glue container, the glue spraying nozzle is connected to the glue container, the glue spraying nozzle is connected to a UV lamp, an insulation device is arranged in the glue container, and the temperature in the glue container is 80°C to 90°C.

[0047] The glue spray nozzle may be a 10PL (picoliter) to 40PL nozzle. For example, the glue spray nozzle may be a 20PL nozzle.

[0048] Input a glue spraying instruction into the control module, wherein the glue spraying instruction includes a glue spraying pattern and a ratio of the spraying area to the battery front area. Figure 4 The spraying module controls the glue spraying module to spray glue in response to the glue spraying instruction.

[0049] Low viscosity glue (10mPa·s) is easy to spread on the battery surface after spraying, and the coating thickness is low, which affects the protection effect. After spraying, the light-curing glue with a viscosity of about 2000mPa·s in this application is not easy to spread, and the single spray coating thickness is 13μm~18μm, with good protection effect and low light reflectivity, and small battery efficiency loss. However, high viscosity glue is easy to clog the nozzle, resulting in uneven spraying, so an insulation device is added to the glue container to keep the temperature at 80℃~90℃ to increase its fluidity.

[0050] Example:

[0051] Taking the total mass percentage content of the glue as 100%, the first glue, the second glue and the third glue provided in the present application are obtained by mixing according to the proportions in Table 1; and the fourth glue of the comparative example is obtained.

[0052] Table 1 Mass fraction ratio of each component of the glue in the embodiment and the comparative example

[0053]

[0054] Embodiment 1:

[0055] The battery cell was tested for its initial battery efficiency using an IV tester, and then a spraying device was used to spray the first glue, the second glue, the third glue and the fourth glue on the front of the back contact battery respectively, according to the conditions of a 20PL nozzle, a resolution of 800 DPI (Dots Per Inch), a glue container temperature of 87°C, and a pattern thickness of 15 μm, to obtain a scratch-resistant battery, and the anti-scratch battery coating area accounted for 2.8% of the front area of ​​the back contact battery. The battery efficiency of the battery cell after spraying was tested using an IV tester, and the difference before and after was calculated to obtain the first spraying electrical loss (△Eta) and the first optical loss (△Isc), and the effect of the glue layer on the battery efficiency was verified. The results are shown in Table 2. It can be understood that, unless otherwise specified, the pattern thickness described in the embodiment of the present application refers to the thickness after the glue is cured.

[0056] The cells with the glue pattern sprayed on them were tested for initial efficiency, and then the cells were sorted at the air outlet (simulating the use process), and then the cell efficiency was tested using an IV tester, and the difference before and after was calculated to obtain the first scratch electrical loss (△Eta), and the protection effect after sorting (sorting the cells) was tested, and the results are shown in Table 3. EL was used to detect scratches (leakage of the substrate was not allowed, scratch length 10mm<L<20mm, scratch rate<0.01%).

[0057] Table 2 Experimental results of different glue spraying efficiency loss

[0058] Glue name First spraying electrical loss △Eta The first optical loss △Isc First glue -0.021 -0.012 Second glue -0.005 -0.010 The third glue -0.053 -0.015 Fourth glue -0.189 -0.037

[0059] Table 3 Anti-scratch test results of different glues

[0060] Glue name Anti-scratch effect First scratch electrical loss △Eta First glue EL has scratches -0.045 Second glue EL no scratch -0.034 The third glue EL no scratch -0.032 Fourth glue EL no scratch -0.152

[0061] The first glue, the second glue and the third glue are the glues provided in the present application. According to the experimental results, the glue provided in the present application has smaller electrical and optical losses and better anti-scratch effect after spraying compared to the fourth glue. It can be seen that the glue and spraying method provided in the present application can solve the problem that the front of the back-contact battery is easily scratched, resulting in reduced conversion efficiency of the battery cell.

[0062] Embodiment 2:

[0063] The cell was tested for its initial cell efficiency using an IV tester, and then a spraying device was used to spray the second glue on the front of the back contact cell with a glue protection pattern according to the pattern thickness, nozzle, resolution and glue container temperature in Table 4, to obtain a scratch-resistant cell, the anti-scratch cell coating area accounting for 2.8% of the cell front area. The cell efficiency of the cell after spraying was then tested using an IV tester, and the difference before and after was calculated to obtain the second spraying electrical loss (△Eta) and the second optical loss (△Isc), verifying the effect of the glue layer on the cell efficiency, and the results are shown in Table 4.

[0064] The cells with the glue pattern sprayed on them were tested for initial efficiency, and then the cells were sorted at the air outlet (simulating the use process), and then the cell efficiency was tested using an IV tester, and the difference before and after was calculated to obtain the second scratch electrical loss (△Eta), and the protection effect after sorting (sorting the cells) was tested, and the results are shown in Table 5. EL was used to detect scratches (leakage of the substrate was not allowed, scratch length 10mm<L<20mm, scratch rate<0.01%).

[0065] Table 4 Spraying device parameters and pattern thickness efficiency loss experimental results

[0066]

[0067] Table 5 Scratch protection test results of different spraying device parameters and pattern thickness

[0068] Graphic thickness Anti-scratch effect Second scratch electrical loss △Eta 13μm EL has scratches -0.042 15μm EL no scratch -0.034 18μm EL no scratch -0.060 25μm EL no scratch -0.135

[0069] It can be seen that when the glue spray thickness is 15μm, the electrical and optical losses of the battery are minimized and the anti-scratch effect is also the best.

[0070] Embodiment three:

[0071] The cell was tested for its initial cell efficiency using an IV tester, and then a spraying device was used to spray the second glue on the front of the back contact cell with a glue protection pattern according to a nozzle of 20PL, a resolution of 800DPI, a spray pattern thickness of 15μm, and a glue container temperature of 87°C, to obtain a scratch-resistant cell, and the spraying area of ​​each group of scratch-resistant cells was different. The cell efficiency of the cell after spraying was tested using an IV tester, and the difference before and after was calculated to obtain the third spraying electrical loss (△Eta) and the third optical loss (△Isc), and to verify the effect of the glue layer on the cell efficiency. The results are shown in Table 6.

[0072] The cells with the glue pattern sprayed on them were tested for initial efficiency, and then the cells were sorted at the air outlet (simulating the use process), and then the cell efficiency was tested using an IV tester, and the difference before and after was calculated to obtain the third scratch electrical loss (△Eta), and the protection effect after sorting (sorting the cells) was tested, and the results are shown in Table 7. EL was used to detect scratches (leakage of the substrate was not allowed, scratch length 10mm<L<20mm, scratch rate<0.01%).

[0073] Table 6 Experimental results of different spraying area proportions and efficiency loss

[0074]

[0075] Table 7 Scratch protection test results with different spraying area ratios

[0076] Graphics ratio Anti-scratch effect Film processing affects △Eta 1.8% EL has scratches -0.021 2.5% EL no scratch -0.019 2.8% EL no scratch -0.016 3.8% EL no scratch -0.047 4.8% EL no scratch -0.048

[0077] It can be seen that when the glue spraying area is 2.8%, the electrical loss and optical loss of the battery are minimal, and the anti-scratch effect is also the best.

[0078] The present application provides a glue and a method for applying the glue. The glue includes a base resin, a functional monomer, a reactive diluent, a photoinitiator and other additives. In the glue, the mass fraction of the base resin is 20% to 35%, the mass fraction of the functional monomer is 5% to 10%, the mass fraction of the reactive diluent is 40% to 55%, and the mass fraction of the photoinitiator is 2% to 6%. The base resin includes methyl methacrylate, styrene and hydroxyethyl methacrylate, and the functional monomer is dimethylaminoethyl methacrylate. The present application also provides a method for applying the above-mentioned glue, wherein the glue is applied to the front of the back contact battery using a printing device or a spraying device to form a protective film, thereby solving the problem that the front of the back contact battery is easily scratched, resulting in a decrease in the conversion efficiency of the battery cell.

[0079] Similar parts between the embodiments provided in this application can be referenced to each other. The specific implementation methods provided above are only a few examples under the general concept of this application and do not constitute a limitation on the protection scope of this application. For those skilled in the art, any other implementation methods expanded based on the scheme of this application without creative work belong to the protection scope of this application.

Claims

1. A glue, characterized in that: The glue comprises a base resin, a functional monomer, a reactive diluent, a photoinitiator and other additives. In the glue, the mass fraction of the base resin is 20% to 35%, the mass fraction of the functional monomer is 5% to 10%, the mass fraction of the reactive diluent is 40% to 55%, and the mass fraction of the photoinitiator is 2% to 6%. The base resin comprises methyl methacrylate, styrene and hydroxyethyl methacrylate, and the functional monomer is dimethylaminoethyl methacrylate.

2. The glue according to claim 1, characterized in that In the glue, the mass fraction of methyl methacrylate is 10% to 15%, the mass fraction of styrene is 5% to 10%, and the mass fraction of hydroxyethyl methacrylate is 5% to 10%.

3. The glue according to claim 2, characterized in that: The active diluent comprises dipentaerythritol hexaacrylate and beta-carboxyethyl acrylate. In the glue, the mass fraction of the dipentaerythritol hexaacrylate is 15% to 20%, and the mass fraction of the beta-carboxyethyl acrylate is 25% to 35%.

4. The glue according to claim 3, characterized in that: The photoinitiator includes 2,4,6-trimethylbenzoyl-diphenylphosphine oxide and methyl benzoylformate.

5. The glue according to claim 4, characterized in that: In the glue, the mass fraction of 2,4,6-trimethylbenzoyl-diphenylphosphine oxide is 1% to 2%, and the mass fraction of methyl benzoylformate is 1% to 4%.

6. A painting method, characterized in that: Applying the glue according to any one of claims 1 to 5, specifically comprising: A coating device is used to coat the front side of the back contact battery to obtain a scratch-resistant battery.

7. The method according to claim 6, characterized in that The anti-scratch battery coating area accounts for 2.5% to 3.8% of the front area of ​​the back contact battery.

8. The method according to claim 7, characterized in that The method is a single-time coating, and the anti-scratch battery surface glue has a thickness of 13 μm to 18 μm after curing.

9. The method according to claim 8, characterized in that The anti-scratch battery coating area accounts for 2.8% of the front area of ​​the back contact battery, and the thickness of the anti-scratch battery surface glue after curing is 15 μm.

10. The method according to claim 6, characterized in that The coating device is a printing device or a spraying device, and the spraying device includes a glue spray nozzle and a glue container. The glue spray nozzle is connected to the glue container, and the glue spray nozzle is connected to a UV lamp. A heat preservation device is arranged in the glue container, and the temperature in the glue container is 80°C to 90°C.